2022
DOI: 10.1016/j.cgh.2021.12.026
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Is Effective in Inflammatory Bowel Disease Patients and Is Not Associated With Disease Exacerbation

Abstract: Background Studies have shown decreased response to COVID-19 vaccinations in some populations. In addition, it is possible that vaccine-triggered immune activation could trigger immune-dysregulation and thus exacerbate inflammatory bowel diseases (IBD). In this population-based study we used the epi-Israeli IBD Research Nucleus (IIRN) validated cohort to explore the effectiveness of COVID-19 vaccination in IBD and to assess its effect on disease outcomes. Methods We inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 19 publications
5
75
0
Order By: Relevance
“…Thus, 21 studies were included in their entirety as shown in Table 1. These included 11 prospective studies, seven retrospective studies and three survey‐based studies 16–21,27–41 . The PRISMA Flow chart is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, 21 studies were included in their entirety as shown in Table 1. These included 11 prospective studies, seven retrospective studies and three survey‐based studies 16–21,27–41 . The PRISMA Flow chart is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…These included 11 prospective studies, seven retrospective studies and three survey‐based studies. 16 , 17 , 18 , 19 , 20 , 21 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 The PRISMA Flow chart is shown in Figure 1 . The study details are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two other cohort studies have found no difference in rates of breakthrough infection following two doses of vaccination 167 168. One Israeli case–control study assessed 12 109 patients with IBD who had received two doses of BNT162b2 vaccine 167.…”
Section: Sars-cov-2 Vaccinationmentioning
confidence: 99%
“…Despite concerns surrounding the robustness of the immune response to vaccination among people being treated with anti-TNF therapies, these same patients do not seem to be at an increased risk of contracting COVID-19 compared with people with IBD not on biological therapy and the age-matched general population. [5][6][7] In fact, anti-TNF use might be a protective factor against severe COVID-19-related outcomes among individuals with autoimmune diseases, 8 which could be due to these therapies inhibiting the maladaptive systemic inflammatory response that often characterises severe COVID-19. This reduction in the risk of severe outcomes might also be related to the association between anti-TNF therapy and reduced IBD-related disease activity; higher levels of disease activity in IBD have been shown to increase the risk of adverse COVID-19-related outcomes.…”
Section: Is the Attenuated Humoral Response To Covid-19 Vaccination I...mentioning
confidence: 99%